Comparative evaluation of zootechnical performance and feather grade in two genetic lines of commercial broilers - Gamboa González, Nidia Fernanda; Cotamo-López, Ariel Leonardo; Suárez-Gómez, Nixon Ali (Spei Domus, 2021)
The genetic improvement programs in broilers are updated based on parameters of interest such as zootechnical performance, yield and quality of the carcass, as well as economic viability. Therefore, the development of new genetic lines that respond positively to the productive challenges of the industry is one of the biggest challenges found today. The objective of this work was to evaluate the zootechnical performance and degree of feathering of the birds during their productive cycle. There were used 2400 male and female broilers, distributed in randomized blocks in a 2 x 2 factorial system (Sex x Line), being two sexes and two genetic lines (line A x Line B) with 12 repetitions per treatment. The birds were distributed in 48 corrals of 2.25 x 1.50 with an initial occupation of 50 birds per corral (14.8 birds/m2), the feeding and lighting program was established by the company. Zootechnical performance parameters were evaluated weekly and the feathering degree on day 41. The data were analyzed by the statistical test of T student and U Mann Whitney’s in data that did not have normal distribution, using the IMB program SPSS 25. No significant differences were observed between the genetic lines evaluated for the variables of body weight, feed consumption, feed conversion, weight gain and efficiency at day 41 of age. With respect to the degree of feathering, the females of the B line presented a greater degree of feathering than the other treatments.